(untitled) (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2016)
Stewardship and colonialism are tightly interrelated. It can be defined as a tendency that stemmed out of the need to appropriate, protect, and guard; it nonetheless resulted in the abduction, deformation, and isolation of heritage from the living populations, as suggested by Latin American and Near Eastern cases. In this paper, we study how colonialism has historically shaped museum stewardship against distinct heritage backgrounds. Selected episodes of stewardship are here used illustrating the twofold background of stewardship; both political and pseudo-scientific enterprise, where stewards, are not mere mediators between past and present, rather pivots of their governmental sponsors’ political interests.